Stock Market Reactions to Interest Rate Changes: Evidence from Emerging Markets - EREN, Binali Selman (The Indonesian Capital Market Review, 2026)
This study investigates the impact of interest rate decisions made by national central banks, including the Federal Reserve (Fed), and the European Central Bank (ECB), on the stock markets of emerging economies. It analyzed stock market reactions to interest rate hikes and cuts through the use of an event study approach. The findings provided evidence of heterogeneous effects of interest rate decisions by national central banks, the Fed, and the ECB on stock markets in emerging economies. Specifically, the results indicated that, in most emerging economies, stock markets reacted negatively to interest rate hikes and positively to cuts by national central banks. However, contrary to expectations, stock markets in many emerging economies reacted positively to interest rate hikes by the Fed and the ECB, but negatively to their interest rate cuts. These findings offer provide policymakers, investors, and portfolio managers with valuable insights into how interest rate decisions impact stock market dynamics in emerging economies.